2008
DOI: 10.1007/s12094-008-0282-x
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ perception of cancer-related fatigue: results of a survey to assess the impact on their everyday life

Abstract: Purpose Fatigue is a cancer-related symptom with great impact on patients' daily lives, but often not discussed with their oncologists. This survey explored functional and psychological fatigue impact among different cancer symptoms according to patient's perception (pp). Methods A cross-sectional, self-administered survey was conducted in 10 oncologist services throughout Spain. Demographical data and tumour diagnoses were collected. Fatigue impact on functional and social activities (Likert scale) and on emo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0
9

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 20 publications
1
24
0
9
Order By: Relevance
“…Persons high on trait anxiety were inclined to seek more support from others, while they also tended to be dissatisfied with the received social support [24,25]. Several studies found that network size decreased due to fatigue [26,27] or to the fact that persons were due to their illness less able to provide support to their social network, which caused an imbalance between the amount of support given to others and the amount of help received by the network [18]. Presumably, this imbalance had a negative impact on their social network.…”
Section: Introductionmentioning
confidence: 99%
“…Persons high on trait anxiety were inclined to seek more support from others, while they also tended to be dissatisfied with the received social support [24,25]. Several studies found that network size decreased due to fatigue [26,27] or to the fact that persons were due to their illness less able to provide support to their social network, which caused an imbalance between the amount of support given to others and the amount of help received by the network [18]. Presumably, this imbalance had a negative impact on their social network.…”
Section: Introductionmentioning
confidence: 99%
“…Fatigue is a common and frequently disabling symptom in cancer survivors 39 that can last for a long time after treatment in some cancer survivors 40 . Fatigue affects the ability to perform daily activities 41 , increases anxiety and depression 42 , and lowers qol in cancer patients 43 .…”
Section: Discussionmentioning
confidence: 99%
“…Ce quatrième volet de résultats présente les comparaisons statistiques des sousgroupes de patients et de médecins, telles qu'elles ont été prévues au protocole de l'étude [1]. Cette analyse est une première dans la litté-rature, d'une part du fait de la rareté des études évaluant la perception des patients sur la fatigue et l'ané-mie chimio-induite, avec ou sans comparaison avec celle des méde-cins, d'autre part du fait que ces études étaient le plus souvent concentrées sur un type de cancer, en majorité des cancers du sein et/ou gynécologiques et, par consé-quent, regroupant plus de femmes [3][4][5]10,11]. L'étude de Díaz et al avait montré que les patients atteints de cancer du sein, de cancer du poumon ou de cancer gastrointestinal citaient tous la fatigue au premier rang des symptômes qui affectaient leur vie quotidienne, mais ne faisait pas de comparaison statistique des sous-groupes [5].…”
Section: Discussionunclassified
“…La prise en charge de la fatigue est donc essentielle. Des études précédentes ont présenté des résultats recueillis auprès de patients atteints de certains types de tumeurs, le plus souvent des cancers mammaires et/ou gynécologiques (ovaires, utérus), sans couvrir l'ensemble des tumeurs les plus fréquemment représentées dans la population [3][4][5]10,11]. L'enquête « Regards croisés 2009 » a été élaborée pour évaluer la perception de la prise en charge de la fatigue en 2009 et comparer l'avis des patients, des méde-cins et des infirmières, afin de mesurer l'évolution des pratiques [1,2,9].…”
Section: Introductionunclassified